Contested utopia : Jewish dreams and Israeli realities - Rosenstein, Marc, 1946- (University of Nebraska Press; The Jewish Publication Society, 2021)
The first volume to examine the Jewish state through the lens of Jewish utopian thought from its biblical beginnings to modernity, Contested Utopia illuminates a kaleidoscope of conflicting utopian visions influencing Israel.